Molecular Fingerprinting Studies Do Not Support Intrahospital Transmission of Candida albicans among Candidemia Patients in Kuwait - Asadzadeh, Mohammad; Ahmad, Suhail; Al-Sweih, Noura; Khan, Ziauddin (Frontiers in Microbiology, 2017)
Candida albicans, a constituent of normal microbial flora of human mucosal surfaces, is a major cause of candidemia in immunocompromised individuals and hospitalized patients with other debilitating diseases. Molecular fingerprinting studies have suggested nosocomial transmission of C. albicans based on the presence of clusters or endemic genotypes in some hospitals. However, intrahospital strain transmission or a common source of infection has not been firmly established. We performed multilocus sequence typing (MLST) on 102 C. albicans bloodstream isolates (representing 92% of all culture-confirmed candidemia patients over a 31-month period at seven major hospitals) to identify patient-to-patient transmission or infection from a common source in Kuwait, a small country in the Middle East where consanguineous marriages are common. Repeat bloodstream isolates from six patients and nine surveillance cultures from other anatomic sites from six patients were also analyzed. Fifty-five isolates belonged to unique genotypes. Forty-seven isolates from 47 patients formed 16 clusters, with each cluster containing 2-9 isolates. Multiple isolates from the same patient from bloodstream or other anatomical sites yielded identical genotypes. We identified four cases of potential patient-to-patient transmission or infection from a common source based on association analysis between patients’ clinical/epidemiological data and the corresponding MLST genotypes of eight C. albicans isolates. However, further fingerprinting by whole genome-based amplified fragment length polymorphism (AFLP) analysis yielded 8 different genotypes, ruling out intrahospital transmission of infection. The findings suggest that related strains of C. albicans exist in the community and fingerprinting by MLST alone may complicate hospital infection control measures during outbreak investigations.